Help‐seeker expectations and outcomes of a crisis support service: Comparison of suicide‐related and non‐suicide‐related contacts to lifeline Australia. (8th June 2022) - O'Riordan, Megan; Ma, Jennifer S.; Mazzer, Kelly; Batterham, Philip; Kõlves, Kairi; Woodward, Alan; Klein, Britt; Larsen, Mark; Goecke, Roland; Gould, Madelyn; Rickwood, Debra
Abstract: Lifeline Australia aims to prevent suicide and support community members in personal crisis via the provision of free anonymous telephone, online chat and text message services. This study aimed to identify the expectations and outcomes of Lifeline help‐seekers, including whether there are differences between suicide‐related and non‐suicide‐related contacts. Help‐seekers ( N = 553) who had previously contacted Lifeline via telephone, online chat, or text message crisis services were recruited via social media and a link provided after Lifeline service use, who completed an online survey about their awareness, expectations and outcomes of Lifeline's services. The responses from help‐seekers who self‐reported suicide‐related and non‐suicide‐related reasons for contact were compared. Participants were highly aware of Lifeline's services, particularly the phone service. The main expectations of all help‐seekers were to feel heard and listened to, feel less upset and feel understood. There were 59.5% of the sample that reported suicidality as a reason for contact. Suicide‐related contacts endorsed more reasons for contact than non‐suicide‐related contacts. Expectations of suicide‐related help‐seekers were greater, but they were less likely to report that their expectations were met. The high expectations and complexity of suicide‐related contacts reveal the challenges in meeting the needs of this high‐priority group, particularly within the context of the multiple demands on crisis support services.